Answer:
The value of x is -4
Explanation:
To solve this problem, we will follow the steps below;
f(x) = -3x + 6 -----------------------------------------------------------------(1)
f(x) = 18
substitute f(x) = 18 in equation (1)
18 = -3x + 6
subtract 6 from both-sie of the equation
18 - 6 = -3x + 6 - 6
12 = -3x
Divide both-side of the equation by -3
12/-3 = -3x /-3
on the right-hand side of the equation, -3 will cancel-out -3 leaving us with just x, while on the left-hand side of the equation 12 will be divided by -3
-4 = x
x= -4
substitute x =-4 into equation (1) to check the solution
f(x) = -3x + 6
f(-4) = -3(-4) + 6 = 12 + 6 = 18